A two-centre study investigating the association between brain natriuretic peptides & outcomes in continuous flow left ventricular assist device recipients - Maria Lambadaris; Farid Foroutan; Julie KK Vishram-Nielsen; Marie Sophie S. Knudsen; Filio Billia; Vivek Rao; Finn Gustafsson; Ana C Alba (Journal of Cardiothoracic Surgery)
Abstract Background Natriuretic peptides are useful prognostic markers in patients with heart failure and this study aims to evaluate the association between N-terminal pro-brain natriuretic peptide and outcomes in patients with a continuous-flow left ventricular assist device. Methods Adult patients with a continuous-flow left ventricular assist device as bridge to transplant or destination therapy and discharged from hospital were included in the study. Multi-variable Cox regression models with natriuretic peptide as a time-dependent covariate modelling multiple measures per patient, and cubic spline analysis were used to evaluate the association between natriuretic peptides and patient outcomes, taking median N-terminal pro-brain natriuretic peptide of 244 pmol/L as the reference value. Heart transplant was considered a competing event for mortality analysis, while death was considered a competing event for transplantation analysis. A multivariable cause-specific Cox regression model evaluated the relationship between natriuretic peptides and heart failure hospitalizations while considering heart failure hospitalizations as recurring events and adjusting for competing risks of death and transplant. Results This retrospective cohort study included 161 adults. During a median follow-up of 4.7 years, 49 patients died, 79 received a heart transplant and 66 were hospitalized for heart failure. In comparison to the median N-terminal pro-brain natriuretic peptide level, patients exceeding 350 pmol/L had a 19% increased mortality (HR 1.19, 95%CI 1.01–1.15) while patients exceeding 330 pmol/L had a 16% higher risk of hospitalization (HR 1.16, 95%CI 1.01–1.12). Conclusion In patients with a continuous-flow left ventricular assist device, serial assessments of natriuretic peptides may help provide personalized patient care.